A Techno-Economic Assessment of 5G Networks with Passive Optical Network-Based Mobile Backhaul and Hybrid Fiber-Copper Fronthaul - Fernandes, André L. P.; Farias, Fabricio S.; Ohashi, Aline A.; Oliveira, Marcos V. P.; Costa, João C. W. A. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2019: Anais do XXXVII Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2019)
Fifth generation (5G) cellular networks will be the key element of a society that is becoming increasingly interconnected and digitalized. Applications adopted in many social and industrial sectors will require from 5G networks higher standards of availability and reliability. These requirements are leading operators to plan the deployment of protection schemes in the backhaul layer. In this context, our aim is to employ simulation to assess in a technical and economic way different backhaul protection schemes based on passive optical network (PON). The results indicates that the use of protection can increase the viability of 5G networks based in a PON backhaul supporting a hybrid fronthaul with fiber and copper.